2020
DOI: 10.1093/ageing/afaa270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dance on cognitive function in older adults: a systematic review and meta-analysis

Abstract: Background dance is a mind–body activity that stimulates neuroplasticity. We explored the effect of dance on cognitive function in older adults. Methods we searched MEDLINE, EMBASE, CENTRAL and PsycInfo databases from inception to August 2020 (PROSPERO:CRD42017057138). Inclusion criteria were (i) randomised controlled trials (ii) older adults (aged ≥ 55 years), (iii) intervention—dance and (iv) outcome—cognitive function. Cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 24 publications
4
38
2
1
Order By: Relevance
“…Studies have shown that dance intervention, as a cognitive stimulus, can stimulate different neural structures to improve various cognitive domains. Subjects can simultaneously learn and memorize new movement patterns, pay attention to follow instructions, execute complex movement patterns, and express emotions and social interactions to stimulate the neural structures that rely on various cognitive functions and improve their neuroplasticity (Hewston et al, 2021 ). However, another dance intervention study for patients with MCI has found that after 3 months of moderate-intensity aerobic dance, the patients' executive function did not improve significantly (Zhu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that dance intervention, as a cognitive stimulus, can stimulate different neural structures to improve various cognitive domains. Subjects can simultaneously learn and memorize new movement patterns, pay attention to follow instructions, execute complex movement patterns, and express emotions and social interactions to stimulate the neural structures that rely on various cognitive functions and improve their neuroplasticity (Hewston et al, 2021 ). However, another dance intervention study for patients with MCI has found that after 3 months of moderate-intensity aerobic dance, the patients' executive function did not improve significantly (Zhu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of dance intervention on patients with MCI is mainly manifested in the following aspects: cognition, psycho-behavioral symptoms, motor functions, and QOL. Systematic reviews have been published on the effect of dance intervention on patients with MCI; current systematic reviews have reached a consensus on the positive effect of dance intervention on global cognition (Chan et al, 2020 ; Meng et al, 2020 ; Zhu et al, 2020 ; Hewston et al, 2021 ; Muiños and Ballesteros, 2021 ). Chan et al have found (Chan et al, 2020 ) that dance can improve the memory function of the older patients with MCI; the study by Zhu et al confirmed this (Zhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Promisingly, a well-designed RCT demonstrated through structural magnetic resonance imaging (MRI) that dancing has superior positive long-term effects on neuroplasticity compared with repetitive or routine exercise. This study was conducted among cognitively healthy older adults (18)(19)(20); thus, the benefits of dance on brain and cognition for older adults with MCI remains to be studied (21). Dance is a mind and body activity, which is demonstrated to improve global cognitive and executive function (21,22), as well as improve balance (18,20), the major control center for which is the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted among cognitively healthy older adults ( 18 20 ); thus, the benefits of dance on brain and cognition for older adults with MCI remains to be studied ( 21 ). Dance is a mind and body activity, which is demonstrated to improve global cognitive and executive function ( 21 , 22 ), as well as improve balance ( 18 , 20 ), the major control center for which is the cerebellum. Interestingly, a ground-breaking study from Chen and Desmond ( 23 ) demonstrated by using functional MRI (fMRI) that cerebellar integrity is associated with cognitive performance highlighting the critical role of cerebellum in non-motor processes expanding the study of neuroplasticity in this area of the brain when studying dance and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Although enthusiasm for dance as a lifestyle intervention has inspired a substantial body of efficacy trials over the past decade, evidence supporting the health benefits of dance has been mixed. For example, a recent meta-analysis examining the cognitive benefits of dance for older people reported improvements to global cognitive function, but inconsistent results across trials for executive function, and no benefit to complex attention, learning and memory (Hewston et al, 2020). Individual differences in previous dance experience, exercise behaviour (McAuley, Mailey et al, 2011), and other physical and psychological factors (Keogh et al, 2009;Stock et al, 2012) are likely to influence capacity for organised dance programs and consequently, program-related outcomes.…”
Section: Introductionmentioning
confidence: 99%